Compromised Rat Testicular Antioxidant Defence System by Hypothyroidism before Puberty - Dipak K. Sahoo; Anita Roy (International Journal of Endocrinology)
Altered thyroid function during early stages of development is known to affect adversely testicular growth, physiology, and antioxidant defence status at adulthood. The objective of the present study is to investigate the modulation of antioxidant defence status in neonatal persistent hypothyroid rats before their sexual maturation and also to identify the specific testicular cell populations vulnerable to degeneration during neonatal hypothyroidism in immature rats. Hypothyroidism was induced in neonates by feeding the lactating mother with 0.05% 6-n-propyl-2-thiouracil (PTU) through the drinking water. From the day of parturition till weaning (25 day postpartum), the pups received PTU through mother's milk (or) drinking water and then directly from drinking water containing PTU for the remaining period of experimentation. On the 31st day postpartum, the animals were sacrificed for the study. An altered antioxidant defence system marked by elevated SOD, CAT, and GR activities, with decreased GPx and GST activities were observed along with increased protein carbonylation, disturbed redox status in hypothyroid immature rat testis. This compromised testicular antioxidant status might have contributed to poor growth and development by affecting the spermatogenesis and steroidogenesis in rats before puberty as indicated by reduced germ cell number, complete absence of round spermatids, decreased seminiferous tubule diameter, and decreased testosterone level.